High rate of stroke and low rate of atrial fibrillation in low socioeconomic strata and blacks: the atrial fibrillation paradox. (25th November 2020) - Kostis, J.B; Zinonos, S; Cabrera, J; Kostis, W.J
Abstract: Background and introduction: Persons living in areas of low socioeconomic status (SES) usually have higher rates of adverse cardiovascular events (CVE) including stroke. Also, atrial fibrillation (AF) is associated with higher rate of CVEs. One would expect that both the rate of stroke and the occurrence of AF would be higher in areas of low SES. Purpose and methods: Using MIDAS, a validated statewide data base of all hospitalizations for cardiovascular disease in NJ with follow up of more than 25 years, we examined the rate of hospitalization for AF by SES in patients with history of myocardial infarction for the years 1995 to 2015 (n=258, 339). Zip codes in New Jersey were aggregated into 4 categories representing quarters of the distribution of SES areas. Results: At one-year follow-up, patients in the lowest SES (lowest 25th percentile) and Blacks were more likely to suffer a stroke (p<0.0001). During one-year follow-up, patients in the lowest 25th percentile (Figure) were significantly less likely (p<0.0001) to be readmitted with a diagnosis of AF. Blacks had lower rate of admission with a diagnosis AF compared to Whites (p<0.0001) (Figure). Cox proportional hazards regression adjusting for demographics and co-morbidities confirmed the validity of these differences. In this analysis patients in the lowest SES quartile and Blacks were less likely to be admitted with AF than those in the highest quartile (HR 0.95, 95% CI 0.92–0.99). Also, Blacks were less likely to be admitted with AF than Whites (HR 0.76, 95% CI 0.71–0.82). This phenomenon (AF paradox) of lower incidence of AF in low SES and in Blacks has been attributed to under-ascertainment of AF in these groups, that may lead to underuse of anticoagulation and result in the occurrence of stroke. Conclusion: Atrial fibrillation is underdiagnosed in patients at low socioeconomic strata and in Blacks and may lead to underuse of anticoagulation and the occurrence of stroke. Special efforts are warranted in detecting AF in these groups. Funding Acknowledgement: Type of funding source: None